Efeito do contexto social e ambiental na emissão de sinais acústicos e visuais em hilídeos noturnos ( amphibia, anura) - Souza, Raíssa Furtado (2014)
The efficiency of intraspecific communication directly affects male reproductive success. Acoustic signaling is the primary form of communication in nocturnal anurans. However, visual signaling can also be important in social interactions. We tested the hypothesis that open environments favor visual signals in a territorial defense context, in a nocturnal tree frog. We established three treatments with eight males of Hypsiboas albomarginatus each: i) Clear Vision, with a mirror without visual obstacles; ii) Obstructed Vision, with half the mirror covered, and iii) Control, with mirror completely covered. We classified behavioral responses into orientation/locomotion, visual display, or acoustic signal. We calculated the mean emission rate per minute per behavior in each treatment, and compared them among treatments using one-way NOVA. Orientation and locomotion, visual display, and the advertisement call did not differ among treatments. However, the emission of aggressive calls in the Obstructed Vision treatment was significantly higher than in the Clear Vision treatment. The lowest rate of aggressive calls occurred in the Control. Thus, visual recognition of an intruder male was enough for resident males to adjust their rate of emission of acoustic aggressive signals, but not visual displays. Therefore, the recognition of the intruder male is not the only feature required for the evolution of visual signals in nocturnal treefrogs during agonistic interactions. This suggests that some visual displays may not be directly used for communication, but rather constitute displacement activity.